Ամիդը Տիգրանակերտ կոչելու հայկական ավանդույթը - Երանյան, Գոռ (Մատենադարան)
The location of the capital city Tigranakert (Tigranocerta of Greco-Roman sources) has always attracted scholarly attention. Most historians agree that it was not Tigran the Great who founded Amid (modern Diyarbakir). The 5th century Armenian authors mention Amid and Tigranakert as different cities, but starting from Matt‘eos Uhayets‘i, later authors confused and identified Amid with Tigranakert. However, some colophons of Armenian manuscripts witness that in the 12th–15th cc., both the inhabitants and outsiders still called the city Amid and not Tigranakert. Probably for the first time, the name Tigranakert appears in a colophon written in 1584, and later it became widespread. It was rather a result of the mass migration of the Armenian population from the southern regions of Armenia to the prosperous Amid in the 15th–16th centuries, where it became majority and tried to give the city an Armenian name sanctified by the authority of the old tradition. As to the modern name of the city, Diyarbakir, it started to be used in the official Ottoman documents after the Armenians had introduced the name Tigranakert. Вопрос о местонахождении столицы Тигранакерт всегда привлекал внимание исследователей. Большинство ученых сходятся в том, что Тигран Великий не основывал Амид (нынешний Диарбекир). Армянские авторы V века упоминают их как разные города; а начиная с Матвея Эдесского они стали их путать или отождествлять. Однако колофоны рукописей свидетельствуют о том, что в XII-XV веках как жители города, так и люди вне его все еще называли его Амидом, а не Тигранакертом. Впервые название Тигранакерт появляется, по-видимому, лишь в колофоне 1584 г. Позднее оно получает широкое распространение. Причина, скорее всего, в том, что армянское насeление, массово мигрировавшее в XV-XVI вв. в процветающий Амид из южных областей Армении и составившее в нем большинство, стремилось дать городу армянское название, притом освященное авторитетом древней традиции. К тому же современное название города, Диярбакр, стало применяться в официальном османском делопроизводстве позже, чем армяне ввели в обращение наименование Тигранакерт.
Keywords: Պատմաբանասիրություն